Tipos de biofertilizantes foliares en el rendimiento de Zea mays Var. Marginal 28T. Zungarococha, Loreto - Perdomo Murayari, Pablo Cesar (2025)
The use of biofertilizers in agriculture is one of the alternatives to produce in a sustained manner and conserving the environment. The Faculty of Agronomy of the National University of the Peruvian Amazon, conducts research on "TYPES OF FOLIAR BIOFERTILIZERS IN THE YIELD OF Zea mays Var. Marginal 28T. ZUNGAROCOCHA, LORETO". The evaluation time was 45 days after the start of the research work, with plots of 5 m x 1.2 m (6 m2), with a Randomized Complete Block Design (RCD), with three treatments and four repetitions, the treatments under study were: T0 (CONTEST), T1 (Biol at 50% + 50% water), T2 (Humus leachate 50% + water 50%). This research work shows us that biofertilizers are included in the green biomass yield of the corn plant and either of the two biofertilizers can be used since statistically they are equal. For the weight of green and dry matter of the treatment T1, 3.53 and 0.84 kg/m2 were obtained. For the weight of green and dry matter of the treatment T2, 3.71 and 0.85 kg/m2 were obtained. In the variable of leaves and stems, the treatment T1 showed the following results of 1.27 and 2.26 kg/m2. In the variable of leaves and stems, the treatment T2 showed the following results of 1.37 and 2.34 kg/m2. With a green matter yield of the whole plant, the yields of 37,100 kilos/ha were obtained for the treatment T2 and 35,300 kilos/ha for the treatment T1.